Dampak Permainan Daring terhadap Aktivitas Belajar Siswa di SD Dharma Mulia - Rudi Muspito; Suranto Suranto; Parsiyono Parsiyono (STAB Maitreyawira, 2022)
The purpose of this study is to determine the impact of online games on the learning activitiesof thestudents of Dharma Mulia Elementary School. This research uses a qualitative type of descriptive research. The data collection techniques used in this study are interviews, observations, and documentation based on the instruments that have been compiled. The data analysis uses data displays to make it easier for readers to understand the research results. The subjects in this study were the Principal, Class V teacher, parents, and the fifth grade Buddhist students at Dharma Mulia Elementary School. The results of this study indicate that the impactof online games for the fifth grade students of Dharma Mulia Elementary School is influenced by the pattern of student play, and the duration of online games which can have an impact of online games on student learning activities. The patterns of playing games are classified in several ways, namely when to play online games, places to play online games, and transactions in online games. The duration of online games played by Dharma Mulia Elementary School students is grouped into several phases, including durations of less than one hour, one to three hours, and more than three hours in one day. The impact of online games on student learning activities shows that there are two impacts, namely the negative impact and the positive impact. The negative impact on student learning activities, among others, on mental activities. and emotional activities. The negative impact on the mental activities is less responsive when learning, and solving problems or that learning achievement decreases. The impact of emotionalactivities on the fifth grade students of Dharma Mulia Elementary School is lack of interest in learning, feels bored, dares, and speaks harshly. The positive impact on the learning activities of Dharma Mulia Elementary School students. The positive impact of the online games on student learning activities, is the high socialization.The application of Visuddhimagga to overcometheonline games can be carried out with several alternative activities. The first activity that can be doneisby advocating or training the studentto practice atthasila andtotraining the studentto meditate either independently or by including the studentin the retreat.